An integrated optimization of lot-sizing and condition-based maintenance policy of a two-stage deteriorating system. (May 2023) - Tian, Sen; Zhang, Nan; Fouladirad, Mitra
Abstract: In this study, a two-stage deteriorating production system is considered. The initiation time of the deterioration follows an exponential distribution. A homogeneous Gamma process is used to model the deterioration propagation process. The equipment produces a single product with a constant production rate and demand rate. To ensure the efficiency of the production, inspection is carried out at the end of each production run. The lot-sizing and the condition-based maintenance threshold are optimized by minimizing the long-run average cost rate, which is derived in the framework of a semi-Markov decision process. The traversal algorithm is used to obtain optimal results. A numerical example is presented to illustrate the applicability of the proposed model. Some sensitivity analysis are carried out in order to highlight the interest and properties of the model. It may provide a theoretical reference for production and maintenance schedules. Highlights: Proposition of a new integrated EPQ and CBM model. Modeling a production equipment with two-stage deterioration process. Deriving the mathematical expression of the long-run cost rate in the framework of the semi-Markov process. Joint optimization of the production lot-sizing and preventive maintenance threshold. Efficiency analysis of the integrated policy through numerical examples to show the applicability of the model.